(untitled) (European Journal of Pure and Applied Mathematics, 2017)
In the present paper, a new class of generalized (r;s,m,φ)-preinvex functions is introduced and some new integral inequalities for the left hand side of Gauss-Jacobi type quadrature formula involving generalized (r;s,m,φ)-preinvex functions are given. Moreover, some generalizations of Hermite-Hadamard type inequalities for generalized (r;s,m,φ)-preinvex functions via Riemann-Liouville fractional integrals are established. These results not only extend the results appeared in the literature (see AkRl, AkYil), but also provide new estimates on these types.